Fronto-temporal cerebriform connective tissue nevus in Proteus syndrome - S M Balaji (Wolters Kluwer Medknow Publications, 2014)
Proteus syndrome is one of the very rare syndromes with occurrence of cerebriform connective tissue nevus. The aim of the present manuscript was to present a case of Proteus syndrome in an unusual facial location, which to the best of our knowledge, is being reported for the first time. The unusual occurrence further strengthens the mosaical basis of its etiopathogenesis.